Effect of Chitosan Edible Coating on the Microbial Quality of Ribbonfish, Lepturacanthus savala (Cuvier, 1929) Steaks - Renuka, V.; Mohan, C. O.; Kriplani, Y.; Sivaraman, G. K.; Ravishankar, C. N. (Fishery Technology, 2016)
The demand for healthy food products without any added chemical preservative is increasing globally. Chitosan can find application in food products due to its bio-preservation effects. The present study was aimed to assess the effectiveness of chitosan edible coating on the microbial quality of ribbon fish, Lepturacanthus savala. Ribbonfish steaks treated with (1%) and without chitosan were packed in multilayered films and stored under refrigerated conditions (3Â±1oC). The fish used in the study is medium fatty fish with good quantity of crude protein. The initial total plate count of 4.5 log cfu g-1 indicates the good quality of fish used in the study which exceeded limit of 7 log cfu g-1 on 10th days in control samples indicating the shelf life of 8-9 days. In chitosan treated samples, total plate counts were observed to be 6.81 log cfu g-1on 15th day and the limit of 7 log cfu g-1was exceeded only on 20th day indicating a shelf life of 16-17 days. This clearly indicates the antimicrobial effect of chitosan. Further, significantly (p<0.01) lower counts for Pseudomonas spp., H2S forming bacteria and enterobacteriaceae were observed for chitosan treated samples. The study reveals that chitosan can be used effectively to enhance the microbial quality as well as shelf life of the fishery products.